The Stereochemistry of Complex Polyketide Biosynthesis by Modular Polyketide Synthases - David H. Kwan; Frank Schulz (Molecules, 2011)
Polyketides are a diverse class of medically important natural products whose biosynthesis is catalysed by polyketide synthases (PKSs), in a fashion highly analogous to fatty acid biosynthesis. In modular PKSs, the polyketide chain is assembled by the successive condensation of activated carboxylic acid-derived units, where chain extension occurs with the intermediates remaining covalently bound to the enzyme, with the growing polyketide tethered to an acyl carrier domain (ACP). Carboxylated acyl-CoA precursors serve as activated donors that are selected by the acyltransferase domain (AT) providing extender units that are added to the growing chain by condensation catalysed by the ketosynthase domain (KS). The action of ketoreductase (KR), dehydratase (DH), and enoylreductase (ER) activities can result in unreduced, partially reduced, or fully reduced centres within the polyketide chain depending on which of these enzymes are present and active. The PKS-catalysed assembly process generates stereochemical diversity, because carbon–carbon double bonds may have either cis- or trans- geometry, and because of the chirality of centres bearing hydroxyl groups (where they are retained) and branching methyl groups (the latter arising from use of propionate extender units). This review shall cover the studies that have determined the stereochemistry in many of the reactions involved in polyketide biosynthesis by modular PKSs.